Direct constraint on the Higgs–charm coupling from a search for Higgs boson decays into charm quarks with the ATLAS detector - Aad, G.; Abbott, B.; Abbott, D. C.; Aliev, M.; Kostyukhin, Vadim V.; Kuchinskaya, Olesya I.; Penzin, Maxim S. (The European Physical Journal C)
A search for the Higgs boson decaying into a pair of charm quarks is presented. The analysis uses proton- proton collisions to target the production of a Higgs boson in association with a leptonically decaying W or Z boson. The dataset delivered by the LHC at a centre-of-mass energy of root s = 13 TeV and recorded by the ATLAS detector corresponds to an integrated luminosity of 139 fb(-1). Flavour-tagging algorithms are used to identify jets originating from the hadronisation of charm quarks. The analysis method is validated with the simultaneous measurement of WW, WZ and ZZ production, with observed (expected) significances of 2.6 (2.2) standard deviations above the background-only prediction for the (W/Z)Z(-> c (c) over bar) process and 3.8 (4.6) standard deviations for the (W/Z)W(-> cq) process. The (WIZ)H(-> c (c) over bar) search yields an observed (expected) upper limit of 26 (31) times the predicted Standard Model crosssection times branching fraction for a Higgs boson with a mass of 125 GeV, corresponding to an observed (expected) constraint on the charm Yukawa coupling modifier vertical bar k(c)vertical bar < 8.5 (12.4), at the 95% confidence level. A combination with the ATLAS (W/Z)H, H -> b<(b)over bar> analysis is performed, allowing the ratio k(c)/k(b) to be constrained to less than 4.5 at the 95% confidence level, smaller than the ratio of the b- and c-quark masses, and therefore determines the Higgs-charm coupling to be weaker than the Higgs-bottom coupling at the 95% confidence level.